Sistem anti-korupsi 4.0: Adopsi teknologi blockchain di sektor publik - Ilima Fitri Azmi; Alih Aji Nugroho (Komisi Pemberantasan Korupsi, 2023)
Countries are using various sophisticated information technologies to help provide quality and transparent services. This research aims to explore the potential and models of using blockchain technology to overcome corruption problems in Indonesia. Proper utilisation of blockchain technology can increase accountability and reduce loopholes in corrupt practices. Blockchain is a distributed database with records (ledgers) shared by all network participants. Smart contract as a form of blockchain can help make the process more transparent and trackable. Since blockchain is a relatively new technology, very few studies have been done to explain its potential in the public sector, particularly with regards to issues of corruption. This study develops a model for the application of blockchain technology and conducts an in-depth analysis of its possibilities using a qualitative method and an exploratory approach. In-depth interviews, designed to get a big picture view of the blockchain development model in the public sector were conducted with several sources, namely the Director General of Asset Tracing KPK (Indonesian Anti-Corruption Commission), KPK Public Prosecutors, the KPK IT department, WIr Group, Financial and Development Oversight Agency (BPKP), and blockchain practitioners. The research was conducted between August and December 2022. The study's findings demonstrate how promising it is to use blockchain technology to lessen corruption. Distributed ledgers give governments new ways to improve transparency. The model that can be applied is ‘permissioned blockchain’ because it has a private nature. Blockchain application requires top management support, organisational readiness, and organisational support. To deepen understanding, further experimental research is needed to test the model.